Pengaturan Dan Penerapan Surat Izin Membuka Tanah Negara Sebagai Syarat Pendaftaran Hak Atas Tanah di Kota Balikpapan: Regulation and Implementation of Issuing a Permit to open a State Land as a Requirement to Register the Right to Land in Balikpapan City - Rahmatika, Nur Auliya; Qurbani, Indah Dwi; Cahyandari, Dewi (Faculty of Law, Universitas Brawijaya, 2023)
This research departs from the Regional Regulation of Balikpapan City Number 1 of 2014 concerning the Permit to open a State Land while the permit is required as proof of land ownership to register the right to land in Balikpapan city. A stamp statement of the land concerned can be used as proof of land ownership for the registration mentioned above. Based on the above issue, this research aims to investigate the problems regarding (1) the regulation of the provision of the permit used to open a state land as a requirement to register the right to land in Balikpapan city and (2) the implementation of the permit used to open a state land as a requirement to register the right to land in Balikpapan city. This research employed socio-legal and socio-juridical methods and took place in Balikpapan as the first city to put the regulation in place regarding the permit mentioned above as a requirement to register the right to land as governed in a Regional Regulation. His research reveals that the Regional Government of Balikpapan City holds the authority to enforce this regulation according to Law Number 23 of 2014 concerning the Regional Government. The implementation of this permit to open a state land as the proof of land ownership in the registration of the right to land in Balikpapan has not been efficient, while people can still refer to the stamp statement to replace this permit document. Therefore, this research suggests that adjustments regarding the regulation be made to assure legal certainty for the people of Balikpapan.